Tracking the distribution of non-professional subtitles to study new audiences - Carmona,David Orrego (2018)
This paper analyzes the consumers in the context of non-professional subtitling (NPS). Using web scraping techniques to collect data about the downloading rate of non-professional subtitles we explore the behavior of consumers. Drawing on the case of the subtitles for House of Cards in Addic7ed.com, a popular multilingual non-professional subtitle distribution website, we describe the consumption of non-professional subtitles and the users response. After outlining the situation of the international audiences for audiovisual products and the relevance of consumers as the driving force behind NPS communities, we analyze the collected data in terms of their interest in the originality of the content and their wish to access the content immediately after it is available. Our findings indicate that the users of non-professional subtitles are highly engaged consumers, eager to access the content as soon as possible and interested in watching it in its original language (English), even with intralingual (same-language) subtitles.